Polysomnography Findings in Patients with Restless Legs Syndrome and in Healthy Controls: A Comparative Observational Study - Homyak, Magdolna (Associated Professional Sleep Societies, LLC, 2007)
STUDY OBJECTIVES: Sleep disturbances and their sequelae are the most common complaints of patients with restless legs syndrome (RLS). We compared polysomnography (PSG) findings in a large cohort of patients with idiopathic RLS and of healthy subjects. DESIGN: Comparative observational study. SETTING: University hospital sleep laboratory. PATIENTS: Age- and sex-matched patients with idiopathic but untreated RLS versus healthy controls. INTERVENTIONS: N/A RESULTS: Each group consisted of 29 females and 16 males. RLS subjects and controls were 47.4 ± 10.9 and 47.3 ± 10.5 years old, respectively. RLS severity was 24.0 ± 6.2 points on the IRLS scale, indicating moderately severe RLS symptoms. We found strong multivariate group effects on PSG parameters (Wilks' lambda, P <0.001): RLS patients exhibited prolonged sleep onset latencies (according to the 10-min criterion but not to the one-epoch criterion), shorter total sleep time, lower sleep efficiency, higher arousal index, higher number of stage shifts, and longer REM sleep latency. During the sleep period time, percentage of wake and sleep stage 1 were increased, and sleep stage 2 and REM sleep were decreased in RLS patients. The PLMS indices and the sleep fragmentation index were markedly increased in the RLS group. CONCLUSIONS: We present the largest polysomnography study to date that compares patients with idiopathic RLS with age- and sex-matched healthy subjects. The findings demonstrate markedly fragmented sleep with deterioration of both NREM and REM sleep in RLS patients. CITATION: Hornyak M; Feige B; Voderholzer U et al. Polysomnography findings in patients with restless legs syndrome and in healthy controls: a comparative observational study. SLEEP 2007;30(7):861–865.